Penentuan Kelompok Persediaan Sparepart Mesin pada Industri Baja dengan Menggunakan Analisis Klasifikasi ABC - M Hudori (JURNAL CITRA WIDYA EDUKASI, 2017)
Inventory is a most important activities in the company. Without the supply, the smooth production will be disrupted or resulted in the machine idle. Inventory can be raw materials or sparepart needed by the company. Machine is a production tool used to produce a product. If a component of the machine is damaged or no replacement available, then the machine can not be used and will be idle. Sparepart needs analysis is needed to avoid the occurrence of these conditions. The ABC classification analysis is a way that can be used to determine the priority of sparepart handling so the company can focus on critical sparepart type. The concept of 80-20 or known as Pareto principle is used to plan inventory based on the ABC classification, especially if there are a considerable number of items. The research method used is descriptive analysis method. The research population is all Ball Bearing types which are used in a national steel industry company, which is 159 types. The sample of the research is Ball Bearing for the last 3 (three) years. The results showed that ABC classification based on usage value was A class of 37 types of Ball Bearing, B class of 44 types and C class of 78 types. The ABC classification results based on the number of usage indicates that only 1 type of Ball Bearing is classified as A, BEARING,BALL,D15/35X11MM-6202-Z, while B class has 10 types and C class there are 26 types.